The founding of Thomas Jefferson's university - Ragosta, John A. 1960-; Onuf, Peter S. 1946-; O'Shaughnessy, Andrew (University of Virginia Press, 2019)
"The Founding of Thomas Jefferson's University examines the development of one of America's oldest and preeminent educational institutions from a wide range of perspectives, considering aspects such as Jefferson's linked intellectual and architectural visions, the often unruly students, the important roles of enslaved people, and the place of the University of Virginia in the context of early American education. The book situates the creation of the university in the context of developments in education in the early republic and the revolutionary changes to which the university contributed"--
Keywords: University of Virginia; Geschichte; Gründung; University of Virginia / History; Jefferson, Thomas / 1743-1826 / Political and social views; Education, Higher / United States / History / 19th century; Jefferson, Thomas / 1743-1826; Education, Higher; Political and social views; United States; 1800-1899; History; Aufsatzsammlung